Possible causes for delay in diagnosis and treatment in head and neck cancer: an institutional study - Agarwal, Nikesh; Singh, Daulat; Verma, Manoj; Sharma, Shantunu; Spartacus, R. K.; Chaturvedi, Manish (International Journal Of Community Medicine And Public Health, 2018)
Background: Head and neck cancer is one of the leading cancers among Indian population. Early diagnosis and treatment is cornerstone for improving survival in any malignancy, any delay leads to advanced form of disease, leading to higher morbidity and mortality. Given the location, head and neck cancers are easily visible or palpable on clinical examination. In spite of this, many patients are diagnosed at advanced stage. Methods: A cross sectional observational study was conducted at a tertiary care center of western india including 156 newly diagnosed head and neck cancer patients. Delay in seeking medical attention was defined as time interval of more than 3 months from the first symptom recognition to the first medical consultation. Subjects were then divided into delay and non-delay group and compared to identify the factors associated with delay in seeking medical attention. Results: Delay in seeking medical consultation was seen in 109 (69.9%) patients. The factors found significantly associated with delay were older age (p<0.001), rural background (p<0.001), illiteracy (p<0.001), joint family (p<0.001), poor socioeconomic status (p<0.001), longer distance from hospital (p<0.001), tobacco chewing (p=0.018), insufficient knowledge (p<0.001) and fear (p=0.031) of the disease. Conclusions: Many of the identified factors for delay in seeking medical attention in head and neck cancer patients are amenable to improvement. Improving health coverage and awareness of available health services, specially in far rural areas could prevent delay in diagnosis and treatment and thus significantly reduce morbidity and mortality as well as burden on health system.